Psychopharmacological assessment of antidepressant-like, anxiolytic, and sedative-hypnotic effects of Tilia platyphyllos Scop. extract using experimental animal models: Antidepressant-like, anxiolytic, and sedative-hypnotic properties of Tilia platyphyllos. - Mehrdad Faizi; Reza Khazaee; Faraz Mojab; Reza Jahani (Iranian Journal of Pharmaceutical Sciences, 2022)
The prevalence of psychiatric disorders namely depression, anxiety, and sleep disturbances has been increased worldwide, particularly during the COVID-19 pandemic. In this regard, the interest of recent investigations is moved toward phytomedicines and bioactive substances derived from natural sources. Although Tilia platyphyllos Scop. contains high amounts of phenolic compounds such as quercetin, kaempferol, and catechin, there is no study on the possible effects of its extract on psychological disorders. The present study was carried out to determine the antidepressant-like, anxiolytic, and sedative-hypnotic effects of the hydroethanolic extract of T. platyphyllos leaves using forced swimming test (FST), tail suspension test (TST), elevated plus maze test (EPMT), pentobarbital-induced loss of righting reflex test and open field test (OFT). Following the ethanolic extraction of T. platyphyllos leaves, the extraction yield was 14% and the total phenolic and total flavonoid contents were found to be 135.23 ± 0.14 mg gallic acid equivalent/g dry extract and 19.02 ± 0.03 mg rutin equivalent/g dry extract, respectively. Both FTS and TST revealed a significant antidepressant-like activity for the tested extract at 400 mg/kg compared to the control group. In addition, the anxiolytic activity of the extract was proven through OFT and EPMT in the same dose. Finally, T. platyphyllos extract at 200 mg/kg and 400 mg/kg significantly increased the sleeping time when compared to the control group reflecting its potential hypnotic activity. Co-administration of T. platyphyllos extract at 400 mg/kg and flumazenil as the GABA-A receptor antagonist decreased the sleeping time but the observed effect was not statistically significant. Therefore, we cannot completely rule out the GABA-A receptor’s involvement in the hypnotic activity of the extract. The biological results presented here led us to conclude that T. platyphyllos extract can be a prominent source of antidepressant, anxiolytic and hypnotic agents. Probably, the main phenolic compounds of T. platyphyllos such as quercetin, kaempferol, and catechin are involved in the observed effects. However, there is still a great need for additional investigations on the exact mechanisms.